The Legitimacy and the Sacredness of Frederick II of Swabia - Vagnoni, Mirko (Eikón / Imago, 2012)
The aim of this article is to analyse the ideological significance and the propagandistic function of the main iconographic characteristics of the official portrayals of the Emperor Frederick II of Swabia on frescos, sculptures, coins and seals. First of all, in order to do this, the fundamental aspects of this iconography related to the Emperor Frederick had to be singled out. After that, the next step was to try to outline which political significance was meant to be propagandized through it: a message, that is, of legitimacy and sacredness founded on the “renovatio” of the ancient Roman Empire and upon the sacred value of the laws. An alternative message, therefore, to that which was based on the coronation rite advocated by the papacy.